The ATLANTIC news studio: reference model and field trial - Teresa Andrade (1997)
Today's available solutions for the production of digitally compressed TV programmes require successive decoding and re-coding operations due both to the multiplicity of digital formats currently in use for signal acquisition and to technology limitations. This has the consequence of increasing the production costs and of reducing the overall signal quality. The ability of using compression also at the production stage will contribute to improve the overall signal quality and to reduce storage requirements and associated costs. The ATLANTIC project (ACTS 078) is developing a digital studio for the production of TV programmes using the MPEG2 format throughout the entire process, from the input of the studio to final programme distribution. EXPO'98, the next international exposition to be held in Lisbon, has been identified as an ideal showcase for audio-visual services developed by ACTS projects. The ATLANTIC project will provide basic infrastructures and technology for compressed-based TV programme production and distribution of audio-visual information and entertainment services for the entire EXPO site. This paper describes the studio reference model of the ATLANTIC project and the role ATLANTIC will be playing within the planned demonstrations of ACTS projects at EXPO'98.